2023
DOI: 10.1093/jac/dkad186
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of treatment adherence on the transmission of HIV drug resistance

Hao Lai,
Rui Li,
Zengbin Li
et al.

Abstract: Introduction A lower adherence rate (percentage of individuals taking drugs as prescribed) to ART may increase the risk of emergence and transmission of HIV drug resistance, decrease treatment efficacy, and increase mortality rate. Exploring the impact of ART adherence on the transmission of drug resistance could provide insights in controlling the HIV epidemic. Methods We proposed a dynamic transmission model incorporating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recent modeling evidence indicated that the importance of 100% adherence level, which found that every 10% decrease in ART adherence would need 5.07% (3.62%) increase in coverage to avoid an increase in HIV infections (deaths). 25 Dose-timing adherence was measured by a question “how often did you take medications within 1 hour of prescribed dose-timing in the past month,” with options including “never,” “occasionally,” “nearly half the time,” “more than half the time (most of the time),” and “all within the prescribed time.” The 1-hour window of dose-timing adherence was based on clinical suggestion and a digital intervention in China. 26 …”
Section: Methodsmentioning
confidence: 99%
“…Recent modeling evidence indicated that the importance of 100% adherence level, which found that every 10% decrease in ART adherence would need 5.07% (3.62%) increase in coverage to avoid an increase in HIV infections (deaths). 25 Dose-timing adherence was measured by a question “how often did you take medications within 1 hour of prescribed dose-timing in the past month,” with options including “never,” “occasionally,” “nearly half the time,” “more than half the time (most of the time),” and “all within the prescribed time.” The 1-hour window of dose-timing adherence was based on clinical suggestion and a digital intervention in China. 26 …”
Section: Methodsmentioning
confidence: 99%